Profiles of Teachers’ Expertise and Professional Development in Technology and Engineering Expertise Program of Vocational Secondary Schools - Istanto Wahyu Djatmiko; Sri Waluyanti; Thomas Sukardi; Lilik Chaerul Yuswono (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
This study was aimed to identify the profiles of teachers' expertise and professional development in Technology and Engineering Expertise Program (TEEP) of Vocational Secondary Schools (VSSs). This study was conducted with a survey approach. The population consisted of 1025 teachers of TEEP at VSSs in Yogyakarta, Indonesia. The samples were 280 teachers selected with proportional random sampling. Data were collected by an open-ended questionnaire and analyzed with a descriptive method. Results of the study identified the profiles of expertise that included the majority of teacher’s employment status is government employees and scanty non-government employees. The range of working time is mostly from 7 and 18 years. Teachers mostly participate in the teachers’ certification through the professional teachers training program.  A few number of the teachers have the additional expertise certificates, and none of the teachers has the dual expertise certificates. Furthermore, types of the teachers’ professional development activities that followed by most of the teachers are seminars, journals, learning media, and participating as members of teachers association.